FORMULASI DAN UJI AKTIVITAS SEDIAAN DEODORANT SPRAY KOMBINASI EKSTRAK DAUN KERSEN (Muntingia calabura L ) DENGAN GARAM MINERAL TERHADAP Staphylococcus epidermidis - Chikita Inaku; Yusi Yusriani (An-Najat, 2024)
Kersen leaves (Muntingia calabura L.) contain flavonoid, saponin, and tannin compounds, while mineral salts primarily contain sodium chloride (NaCl), which serves as an antibacterial agent. The aim of this research is to formulate kersen leaf extract with mineral salts as a deodorant spray. The research method was conducted through laboratory experiments, where kersen leaves were macerated using 96% ethanol solvent, and then formulated into deodorant spray preparations with various concentrations: FI (5% extract, 15% mineral salts), FII (10% extract, 15% mineral salts), and FIII (15% extract, 15% mineral salts). The parameters observed in this research include pH test, organoleptic, homogeneity, spreadability, drying time, irritation, cycling test, and activity test of the preparation. The results of the study showed that the deodorant spray preparations met the test parameter requirements, and the bacterial test results 0.000<0.05 indicated significant data differences and the average diameter of the inhibition zone against Staphylococcus epidermis bacteria. The conclusion is that the combination of kersen leaf extract (Muntingia calabura L.) with mineral salts can be formulated into a deodorant spray preparation. The combination of kersen leaf extract (Muntingia calabura L.) with mineral salts exhibits antibacterial activity in inhibiting the growth of Staphylococcus epidermis bacteria.